The Bicol river basin development program the temporal dimension in functional coordination - Astillero, Emmanuel I. (1981)
The problem of development during the last decade became more complex be- cause of the recognition of three concepts: (1) integrating functionally- related sectoral programs within a larger development strategy is a more effective approach in effecting socio-economic goals; (2) spatial integration is crucial to attaining social equity in development, and (3) participants in development must share the same time perception. Optimal management decisions within complex development programs can be approximated only with the proper synchronization, sequence and rate of activities, in the context of both rational and environmental time. Two briefcase studies within the experience of the Bicol River Basin Development Program (BRBDP) tend to show that realistic schedules, attention to the timing, the synchronization of time perception of the lending agency and the project implementors, and the sequencing and rate of events, are important dimensions in project management.
Keywords: Rural development projects -- Case studies; Rural development projects -- Environmental aspects; Rural development projects -- Sociological aspects; Irrigation farming; National Irrigation System; Bicol River Basin Development Program